Provenance of Pleistocene Sediments in West Sarawak and Evidence for Pliocene Acid Magmatism in Central Borneo - H. Tim Breitfeld (Ikatan Ahli Geologi Indonesia, 2021)
Quaternary deposits in Borneo are commonly not assigned to any formation or group and are usually not studied in great detail but are important for understanding of the Pleistocene to Holocene climate and drainage evolution. This study presents a detrital zircon provenance analysis of two possible (Plio-) Pleistocene fluvial deposits in West Sarawak, indicating two very different source areas and paleo-river drainages. Those paleo-rivers resemble the present-day drainage but show much higher energy level deposits associated with higher sedimentation rates possibly as a function of (Plio-) Pleistocene climate and hinterland exposure. The deposits at Kampung Jangkar in western West Sarawak were entirely sourced by the uplifted Pueh batholith. In contrast, sediments in Petra Jaya district (northern Kuching city) were sourced by recycling of the Kayan Sandstone near the Bungo Range in the area of the town Bau. The Petra Jaya sediments have abundant Pliocene and some Late Miocene zircons. The Niut Volcanics south of West Sarawak are of this age, but are basic and could not yield significant zircons. It is therefore concluded that zircons came from acid igneous rocks of Pliocene age, as well as the Kayan Sandstone and Middle Miocene Bau Suite igneous rocks, where they formed a highland in the Bau-Bungo Range region which has been entirely removed by erosion.